2011
DOI: 10.1083/jcb.201010034
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific targeting of PKA to multivesicular bodies

Abstract: PKA RIα subunit is localized to MVBs by the A-kinase–anchoring protein AKAP11 when disassociated from the PKA catalytic subunit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 61 publications
1
34
1
Order By: Relevance
“…It has previously been suggested that mTOR may be activated by deletion of Prkar1a and may directly interact with Prkar1a (24), although these data are somewhat controversial (25). Additionally, mTOR activation by TSH has been suggested to be, at least partly, due to PKA phosphorylation of the target of rapamycin complex 1 complex member PRAS40 (26).…”
Section: Discussionmentioning
confidence: 98%
“…It has previously been suggested that mTOR may be activated by deletion of Prkar1a and may directly interact with Prkar1a (24), although these data are somewhat controversial (25). Additionally, mTOR activation by TSH has been suggested to be, at least partly, due to PKA phosphorylation of the target of rapamycin complex 1 complex member PRAS40 (26).…”
Section: Discussionmentioning
confidence: 98%
“…In mammalian cells, the MVBs play a positive role in activating Wnt signaling, by sequestering the inhibitor (GSK3) within the ILVs [44]. In another example, the free RIα subunit of cPKA is sequestered onto the surface of MVB's by AKAP11 in a cAMP dependent manner [42]. Finally, the integrity of the late endosomes is crucial for amino-acid and insulin stimulated mTOR signaling [43].…”
Section: Discussionmentioning
confidence: 99%
“…Endosomes are known to serve functions beyond cargo sorting. Recent findings suggest that endosomal compartments additionally function as signaling anchors/platforms, integrating membrane trafficking and intracellular signal transduction [42], [43], [44], [45], [46], [47].…”
Section: Introductionmentioning
confidence: 99%
“…Although RI subunits were typically found to be more diffuse in the cytoplasm than RII subunits, they could also be recruited in a more dynamic way as evidenced by the migration of RI to the cap site in activated lymphocytes (45) and following treatment of cardiac myocytes with H 2 O 2 (46). Furthermore, it was shown that overexpressed RI␣ and C subunits were still associated with AKAP220 even though they were diffuse in the cytoplasm; however, targeting of the RI␣ subunit to multivesicular bodies only occurred upon activation of the complex (47).…”
Section: Discussionmentioning
confidence: 99%